Heat Stress Exposure and Chronic Kidney Disease in Indonesian Rayon Factory Workers (Majalah Kedokteran Bandung, 2025)
Chronic kidney disease (CKD) has become an emerging occupational health concern, particularly among workers exposed to high temperatures. This study aimed to determine the prevalence of CKD among workers in a rayon factory in West Java, Indonesia, and evaluate its association with occupational heat exposure. A retrospective cohort study was conducted using secondary data from the company’s annual medical check-up records (2022–2023) and workplace heat stress measurements obtained in 2017 using the Quest Temp Wet-Bulb Globe Temperature monitor. Workers who completed medical examinations in both years and gave written informed consent to participate in the study were included. CKD was defined as a serum creatinine level >1.2 mg/dL and an estimated glomerular filtration rate
Keywords: Chronic kidney diseases; heat stress; Indonesia; workers